Interaction between Chromosomal Protein HMGB1 and DNA Studied by DNA-Melting Analysis - Chikhirzhina, Elena V.; Tatiana, Starkova J.; Polyanichko, Alexander M. (Journal of Spectroscopy, 2014)
Interaction of HMGB1 nonhistone chromosomal protein with DNA was studied using circular dichroism spectroscopy and thermal denaturation of DNA. Melting DNA in the complex was shown to be a biphasic process. The characteristic melting temperatures of unbound DNA and the DNA bound to HMGB1 in 0.25 mM EDTA solutions were found to be TmI=44.0±0.5°C and TmII=62.0±1°C, respectively. It was shown that the binding of the HMGB1 molecule affects the melting of the DNA region approximately 30 b.p. long.